1995
DOI: 10.1093/jac/36.2.395
|View full text |Cite
|
Sign up to set email alerts
|

Bioavailability of fluconazole administered via a feeding tube in intensive care unit patients

Abstract: Fluconazole, a triazole compound with potent activity against many medically important fungi, undergoes rapid oral absorption, and has been shown in healthy volunteers to exhibit virtually complete bioavailability. The purpose of this study is to evaluate the bioavailability of fluconazole administered via a feeding tube with concomitant enteral feeds in intensive care unit patients. Once prescribed by the attending physician, fluconazole was administered either as an intravenous infusion over 1 h or the table… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0
2

Year Published

1997
1997
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(25 citation statements)
references
References 0 publications
2
21
0
2
Order By: Relevance
“…Several published reports discuss the use of nasogastric and other types of enteral feeding tubes to administer azole antifungals, including fluconazole (1,14,19), itraconazole (15), and voriconazole (7,12,13).…”
Section: Discussionmentioning
confidence: 99%
“…Several published reports discuss the use of nasogastric and other types of enteral feeding tubes to administer azole antifungals, including fluconazole (1,14,19), itraconazole (15), and voriconazole (7,12,13).…”
Section: Discussionmentioning
confidence: 99%
“…NGT dosing has been shown to offer cost-savings and to decrease the risk of secondary infection from indwelling intravenous catheters in some cases. 11,12 NGT administration of voriconazole can be an alternative to i.v. treatment of suspected or documented fungal infections in mechanically ventilated patients by simplifying the treatment and reducing its cost.…”
Section: 9mentioning
confidence: 99%
“…The latter can simplify drug administration and reduce costs significantly. Nicolau et al demonstrated excellent bioavailability of fluconazole administered via a feeding tube in critically ill patients without recent gastro-intestinal (GI) surgery and normal renal and hepatic function [8]. Rosemurgy et al found a bioavailability of 77 % after a single dose of 100 mg in four patients with recent GI surgery [9].…”
Section: Introductionmentioning
confidence: 99%